Peran Public Relations Lembaga Amil Zakat LMI Meningkatkan Brand Image - Muhamad Irfan Nurdiansyah; Edelweis Putri Prima; Anita Agustina Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Public Relations or PR is very important in a company, PR bridges communication between the company and the community/clients. One of the main tasks of public relations is to improve the company's brand image with the aim that the public/clients are aware of the position or existence of the company. The author raised this title because public relations have an important role in building and improving the brand image of a company. The purpose of this paper is to determine the role of public relations carried out by Lembaga Manajemen Infaq (LMI) in improving brand image. This research uses qualitative research with descriptive data analysis techniques. The author tried to present a description of a company. This study uses data collection techniques through field observations, interviews with personal assistant directors and digital managers and using LMI documentation. The results showed that public relations at LMI has a role to educate, provide information, and service to the public, provide data transparency and increase sales of the institution. As for the supporting factors in improving the brand image are experienced HR and LMI certified as LAZ. While the inhibiting factor is the absence of a limited public relations department and regional offices that have not been spread throughout Indonesia.